2011
DOI: 10.2165/11206740-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Indomethacin/Prochlorperazine/Caffeine

Abstract: The indomethacin/prochlorperazine/caffeine fixed combination (Difmetré®) combines the NSAID indomethacin with the phenothiazine antiemetic prochlorperazine and caffeine. It is currently available as two oral (effervescent tablet and coated tablet) and two rectal (suppository and low-dose suppository) formulations. Oral and rectal formulations of indomethacin/prochlorperazine/caffeine were effective and generally well tolerated in the treatment of migraine and episodic tension-type headache (TTH) in adult patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…25,26 Notably, two drug−drug cocrystals involving IND are already known, namely, IND−carbamazepine 27 and IND− lidocaine. 28 CAFF was chosen as a coformer because it can be found together with IND, owing to their synergic effects, 29 in Difmetre, a pharmaceutical containing IND, CAFF, and prochlorperazine dimaleate in a molar ratio 1:5.6:0.07. Difmetreć an be administered as a film-coated or effervescent tablet or as a suppository and is currently used to treat strong migraines, especially hypnic headaches.…”
Section: ■ Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…25,26 Notably, two drug−drug cocrystals involving IND are already known, namely, IND−carbamazepine 27 and IND− lidocaine. 28 CAFF was chosen as a coformer because it can be found together with IND, owing to their synergic effects, 29 in Difmetre, a pharmaceutical containing IND, CAFF, and prochlorperazine dimaleate in a molar ratio 1:5.6:0.07. Difmetreć an be administered as a film-coated or effervescent tablet or as a suppository and is currently used to treat strong migraines, especially hypnic headaches.…”
Section: ■ Introductionsupporting
confidence: 66%
“…IND often has been selected as the main API of many cocrystals found in the literature: for example, cocrystals of IND with saccharine and with nicotinamide have been extensively investigated to examine their structure and biological effects. , Notably, two drug–drug cocrystals involving IND are already known, namely, IND–carbamazepine and IND–lidocaine . CAFF was chosen as a coformer because it can be found together with IND, owing to their synergic effects, in Difmetré, a pharmaceutical containing IND, CAFF, and prochlorperazine dimaleate in a molar ratio 1:5.6:0.07. Difmetré can be administered as a film-coated or effervescent tablet or as a suppository and is currently used to treat strong migraines, especially hypnic headaches.…”
Section: Introductionmentioning
confidence: 99%
“…This data lends support to the notion that caffeine can be absorbed into systemic circulation when administered via the rectum or colon. It has been demonstrated that a single administration of rectal formulation of indomethacin/prochlorperazine/caffeine containing 75 mg of caffeine in adult patients with migraine and episodic tension-type headache exhibited averaged C max⁡ of 5.2  μ g/mL and averaged T max⁡ of 1.9 h [32]. In contrast, the present study revealed that a single administration of 500 mL of coffee enema fluid containing a comparable content of caffeine (107.24 mg) resulted in a remarkably lower extent ( C max⁡ and AUC) but faster T max⁡ (0.30 h or 18 min) of absorbed caffeine.…”
Section: Discussionmentioning
confidence: 99%
“…Unilateral headache is a diagnosis feature of both migraine and hemicrania continua (1). A few patients with migraine also benefit from treatment with indomethacin which can further contribute to diagnostic confusion (29,30). However, there remains clear differences between hemicrania continua and migraine.…”
Section: Discussionmentioning
confidence: 99%